(untitled) (International Journal of Food and Nutritional Sciences, 2022)
We now live and operate in a technologically advanced world. It has helped remove tangible constraints that once prevented people from cooperating smoothly across borders. Businesses today are realising that they must change if they want to compete with technology giants like Amazon, Google, and Facebook, which have perfected the art of global service distribution. Traditional colleges are reducing expenses by switching to blended learning, a less expensive form of instruction, in order to remain competitive. This study examines the effects of implementing integrated learning in management education. The study’s findings demonstrate that, in comparison to traditional learning, the use of blended learning in management education has a significant effect on student engagement. It also reveals that the use of blended learning in management education has a big effect on how happy the students are. The present study will be helpful to education sector for the academic development of students.